CHARACTERIZATION AND HABITATS OF BACTERIA AND YEASTS ISOLATED FROM LAKE VANDA IN ANTARCTICA (Eleventh Symposium on Polar Biology) - ナガシマ, ヒデユキ; ニシカワ, ジロウ; マツモト, ゲンキ; イイズカ, ヒロシ; NAGASHIMA, Hideyuki; NISHIKAWA, Jiro; MATSUMOTO, Genki I.; IIZUKA, Hiroshi (National Institute of Polar Research, 1990)
P(論文) Several strains of bacteria and yeasts were isolated at various depths of a meromictic lake, Lake Vanda, to clarify their physiological properties in relation to their habitats. Gram-negative rods, strains T-1, T-2, T-6, T-14, 3B, and Pseudomonas sp. 3G, were isolated at depths of above 30m where the temperature is 5-7℃ and the chlorinity is low. T-1, T-6, 3B, and 3G grow aerobically below 27℃, optimally about 20℃ under low salt concentration (<1% NaCl). Gramnegative aerobic cocci, strains 13A-F, were isolated at a depth of 69m near the bottom where the temperature is 24℃ and the chlorinity is high, up to 76.5 g/kg. Strain 13A grows aerobically at 12-36℃, optimally about 30℃ under the addition of 0 to 10% NaCl to the culture medium. T-1, T-6, 3G, and 13A contain more than 81% of unsaturated fatty acids such as oleic acid (18:1) and palmitoleic acid (16:1). The yeast Candida sp. strains T-3, T-4, T-5, T-9, and T-11 isolated at a depth of 5 m grow below 25℃, optimally about 15℃. They are fermentable and can utilize various sugars such as glucose and sucrose. T-5 and T-9 have 74% and 86% of unsaturated fatty acids such as linoleic acid (18 :2), respectively. The presences of psychrophilic bacteria and yeasts in the water column (5-30m), and of halotolerant bacteria in the bottom water (69m) well correspond to the meromictic property of the lake. departmental bulletin paper